2022
DOI: 10.1038/s41467-022-29397-z
|View full text |Cite
|
Sign up to set email alerts
|

MTAP deficiency creates an exploitable target for antifolate therapy in 9p21-loss cancers

Abstract: Methylthioadenosine phosphorylase, an essential enzyme for the adenine salvage pathway, is often deficient (MTAPdef) in tumors with 9p21 loss and hypothetically renders tumors susceptible to synthetic lethality by antifolates targeting de novo purine synthesis. Here we report our single arm phase II trial (NCT02693717) that assesses pemetrexed in MTAPdef urothelial carcinoma (UC) with the primary endpoint of overall response rate (ORR). Three of 7 enrolled MTAPdef patients show response to pemetrexed (ORR 43%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 54 publications
1
19
1
Order By: Relevance
“…The relationship of CDKN2A and CDKN2B expression with the corresponding SCNA levels seemed to indicate that complex pathways regulated their transcription levels and that their tumor suppressor properties were not evident in ccRCC. MTAP is another tumor suppressor in Del(9p21.3) ( 63 65 ). Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of CDKN2A and CDKN2B expression with the corresponding SCNA levels seemed to indicate that complex pathways regulated their transcription levels and that their tumor suppressor properties were not evident in ccRCC. MTAP is another tumor suppressor in Del(9p21.3) ( 63 65 ). Xu et al.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, SCNAs, notably losses containing IFNs and IFN pathway genes, many on chromosome 9p, have been reported to predict immune-cold, immune checkpoint therapy (ICT)-resistant tumors ( 1 , 21 ). Immunogenetic studies of 9p21.3 copy number alterations, focused primarily on CDKN2A deletion ( 22 , 23 ), can encompass a cluster of 16 type-I IFN genes ( Fig. 1 A ) involved in antitumor immune responses ( 24 ), while IFN-γ pathway gene alterations at 9p24.1 have been reported to correlate with immune-cold, ICT-resistant tumors, primarily in metastatic melanoma ( 25 ).…”
mentioning
confidence: 99%
“… 15 9p21.3 loss has been reported to correlate with a cold tumor immune microenvironment and primary resistance to single-agent ICT. 19 Nonetheless, several strategies are actively being developed in combination with immune checkpoint blockade to modulate the tumor immune microenvironment in various solid cancers with 9p21.3 loss, such as antifolates, 20 PRMT inhibitors, 21 anti-adenosine, 20 and CDK4/6 inhibitors. 22 In this context, Sun et al recently showed that tRCC are cold tumors when compared with clear-cell RCC, with the exception of a subset harboring MED15-TFE3 fusions.…”
Section: Discussionmentioning
confidence: 99%